2013
DOI: 10.1242/jeb.094573
|View full text |Cite
|
Sign up to set email alerts
|

Blood feeding induces hemocyte proliferation and activation in the African malaria mosquito, Anopheles gambiae Giles

Abstract: Malaria is a global public health problem, especially in sub-Saharan Africa, where the mosquito Anopheles gambiae Giles serves as the major vector for the protozoan Plasmodium falciparum Welch. One determinant of malaria vector competence is the mosquito's immune system. Hemocytes are a critical component as they produce soluble immune factors that either support or prevent malaria parasite development. However, despite their importance in vector competence, understanding of their basic biology is just develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 55 publications
(95 reference statements)
9
90
2
Order By: Relevance
“…4C). In GFP-silenced mosquitoes fed with the noninvasive MAOP parasite, ∼25% of the perfused hemocytes incorporated the EdU label, similar to previous reports that demonstrated that blood feeding promotes hemocyte proliferation (19,23). When GFP-silenced mosquitoes were fed with wild-type parasites, ookinete traversal triggered a significant increase in EdU-labeled hemocytes, but this increase was abrogated by LL3 silencing (Fig.…”
Section: Significancesupporting
confidence: 88%
See 3 more Smart Citations
“…4C). In GFP-silenced mosquitoes fed with the noninvasive MAOP parasite, ∼25% of the perfused hemocytes incorporated the EdU label, similar to previous reports that demonstrated that blood feeding promotes hemocyte proliferation (19,23). When GFP-silenced mosquitoes were fed with wild-type parasites, ookinete traversal triggered a significant increase in EdU-labeled hemocytes, but this increase was abrogated by LL3 silencing (Fig.…”
Section: Significancesupporting
confidence: 88%
“…Hemocytes appear to be the primary phagocytic cells that eliminate bacterial pathogens (29) and are thought to produce several hemolymph components involved in pathogen recognition and immune clearance (4,30). Evidence suggests that hemocytes undergo proliferation and an increase in overall hemocyte numbers in response to a blood meal (19,23), as well as aggregate in response to immune challenge (24). Following a Plasmodium-infected blood meal, mosquito hemocyte transcripts respond specifically to parasite infection, suggesting that hemocytes may have an integral role in modulating mosquito immunity (22,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immune system relies upon the actions of several types of immune cells called hemocytes, which are primary regulators of these immune responses (Tsakas and Marmaras 2010;Bhikshapati et al 2012). Hemocytes kill pathogens either by phagocytosis, encapsulation, production of free radicals of nitrogen and oxygen, or by the production of soluble antimicrobial factors (Rodrigues et al 2010;Bryant and Michel 2014). The immune system of insect identifies invading microorganism using pattern recognition receptors (PRRs) encoded on their germ line, which is then countered by both humoral and cellular reaction ( González-Chávez et al 2009).…”
Section: Introductionmentioning
confidence: 99%